1973
DOI: 10.2136/sssaj1973.03615995003700020015x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Saturating Cations on the Adsorption of Dasanit®, O,O‐diethyl O‐[p‐(methyl sulfinyl) phenyl] phosphorothioate, by Montmorillonite Suspensions

Abstract: A study was conducted to examine the adsorptive behavior of Dasanit in montmorillonite suspensions as affected by saturating cations and the clay suspension concentration. Adsorption isotherms, similar to Type III or Class “S” isotherms, were constructed for 10 cation‐saturated montmorillonites. Infrared spectroscopy was used to examine the relative polarities of the sulfoxide, sulfone, phosphoryl, and carbonyl groups as they occur in Dasanit, in some of its oxidation products, and in several other insecticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Mechanisms were similar to those proposed for parathion, i.e., hydrogen bonding via water bridges between polar func tional groups and adsorbed cations (Bowman et al 1970;Bowman 1973;Singhal and Singh 1978).…”
Section: +supporting
confidence: 60%
See 1 more Smart Citation
“…Mechanisms were similar to those proposed for parathion, i.e., hydrogen bonding via water bridges between polar func tional groups and adsorbed cations (Bowman et al 1970;Bowman 1973;Singhal and Singh 1978).…”
Section: +supporting
confidence: 60%
“…Bowman (1973) found that the saturating cation on montmorillonite affected adsorption of fensulfothion in the following order of retention:…”
Section: +mentioning
confidence: 99%
“…A number of studies (e.g., Bowman, 1973;Bowman and Sans, 1977;Yaron and Saltzman, 1972;Gerstl and Yaron, 1978;Yaron, 1978) on the interaction of these and other organophosphate esters with various clays in aqueous and nonpolar media have shown that the adsorption of organophosphate esters on a clay surfaee is highly dependent on the exchangeable cation and its hydration state. Previous studies investigated the low part of the adsorption isotherms; yet, if clays are to be used as carriers for pesticides or other bioactive substances, it is important, for example, to study the interactions oforganophosphate esters on clays at high surface concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This view is exemplified by the reliance on soil organic carbon-normalized sorption coefficients (K OC ) to predict the fate and transport of organic compounds in soils. However, several recent studies and a few earlier ones provide clear evidence that soil minerals can function as effective adsorbents for pesticides and organic contaminants under environmentally relevant conditions (Bailey et al, 1968;Bowman, 1973;Boyd et al, 2001;Celis et al, 1998;Haderlein et al, 1996;Hundal et al, 2001;Johnston et al, 2002;Laird et al, 1992;Mortland, 1970;Sheng et al, 2002;Zhu et al, 2004). For important categories of pesticides (e.g., triazines, carbamates, ureas, nitrophenols, benzonitrile) and organic contaminants (e.g., nitroaromatics), sorption by clays can be equal or greater than that by SOM based on comparisons of sorption by a unit mass of isolated clay minerals vs. SOM and by synthetic clay-organic matter complexes (Li et al, 2003;Sheng et al, 2001).…”
mentioning
confidence: 99%